Northern Lights, Volume 4. - Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2004)
"Northern Lights, Volume 4" by Gilbert Parker is a collection of stories written in the late 19th century. The volume encompasses various narratives set against the backdrop of the Canadian North, exploring themes of endurance, faith, and the interplay between civilization and the wild. The opening story, "A Man, A Famine, and A Heathen Boy," introduces us to William Rufus Holly, a lazy but educated man who takes on the daunting task of becoming a missionary in the harsh landscapes of Athabasca. At the start of the narrative, we learn about the challenges and beauty of life in Athabasca, a land known for its extreme winters and vibrant, lively summers. William Rufus Holly, also referred to as "Sleeping Beauty," embarks on a journey north, motivated by a desire to make something of himself despite his previous life of indolence. His arrival is met with skepticism by the local Athabasca Indians, particularly when he attempts to establish his role as a missionary. The story quickly escalates into a dramatic moment when Holly risks his life to save a drowning boy, marking a significant turning point that earns him respect and paves the way for his future mission. This initial segment sets the stage for exploring the themes of redemption, resilience, and the struggle between different cultures. (This is an automatically generated summary.)
A man, a famine, and a heathen boy -- The healing springs and the pioneers -- The little widow of Jansen -- Watching the rise of Orion.
Release date is 2004-07-01
This eBook was produced by David Widger
Keywords: Canada, Northern -- Fiction; Short stories, Canadian